Hydrogels based on low-methoxyl amidated citrus pectin and flaxseed gum formulated with tripeptide glycyl-l-histidyl-l-lysine improve the healing of experimental cutting wounds in rats - Synytsya, Alla; Poučková, Pavla; Zadinová, Marie; Troshchynska, Yana; Štětina, Jiří; Synytsya, Andriy; Saloň, Ivan; Král, Vladimír (International journal of biological macromolecules, 2020)
Hydrogels based on natural and modified polysaccharides represent growing group of suitable matrices for the construction of effective wound healing materials. Bioactive tripeptide glycyl-l-histidyl-l-lysine and amino acid α-l-arginine are known to accelerate wound healing and skin repair. In this study, hydrogels based on low-methoxyl amidated citrus pectin or flaxseed gum were prepared and used for the transport of these healing agents to the experimental cutting wounds affected by extensive skin damage. Fourier-transform infrared spectroscopy, rheology, differential scanning calorimetry, scanning electron microscopy, swelling and release tests confirmed that these hydrogels differed in structure and physical properties. The cationic tripeptide was found to bind to carboxylic groups in LMA pectin, and the C3OH hydroxyl and ring oxygen O5 are involved in this interaction. The pectin hydrogel showed high viscosity and strong elastic properties, while the flaxseed gum hydrogel was characterised as a viscoelastic system of much lower viscosity. The former hydrogel released the drugs very slowly, while the latter hydrogel demonstrated zero order releasing kinetics optimal for drug delivery. In the in vivo wound healing testing on rats, both polysaccharide hydrogels improved the healing process mediated by the mentioned biomolecules. The tripeptide applied in the hydrogels showed significantly higher healing degree and lower healing time than in the control animals without treatment and when it was applied in an aqueous solution. Despite the absence of a synergistic effect, the mixture of the tripeptide and α-l-arginine in the hydrogels was also quite effective in wound healing. According to histological analysis, complete healing was achieved only when using the tripeptide in the flaxseed gum hydrogel. These observations might have an important prospect in clinical application of polysaccharide hydrogels.
Keywords: hojení ran; Humans; Low methoxy amidated pectin; Oligopeptides; hydrogely; Pectins; Flax; kůže; Microscopy, Electron, Scanning; krysa rodu Rattus; Gingiva; lidé; zvířata; oligopeptidy; Wound Healing; gingiva; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; mikroskopie elektronová rastrovací; Flaxseed gum; Hydrogels; Rats; Polysaccharide hydrogels; Animals; Wound healing; Bioactive peptides; len; Skin; pektiny